2009
DOI: 10.1016/j.jacc.2009.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Supported High-Risk Percutaneous Coronary Intervention With the Impella 2.5 Device

Abstract: This large multicenter registry supports the safety, feasibility, and potential usefulness of hemodynamic support with Impella 2.5 in high-risk PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
145
3
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 214 publications
(160 citation statements)
references
References 10 publications
8
145
3
4
Order By: Relevance
“…It is likely that staging of these procedures reflects the high degree of coronary and patient complexity being treated in contemporary PCI practice, 4 including the need for careful evaluation of therapeutic options or medical stabilization and application of adjunctive therapies such as ventricular support devices. 22 However, given the high degree of hospitallevel variability in multivessel disease management noted in our analysis, it appears that local practice patterns may be an important driver of the decisions surrounding staging of procedures as well.…”
Section: Staged Revascularizationmentioning
confidence: 83%
“…It is likely that staging of these procedures reflects the high degree of coronary and patient complexity being treated in contemporary PCI practice, 4 including the need for careful evaluation of therapeutic options or medical stabilization and application of adjunctive therapies such as ventricular support devices. 22 However, given the high degree of hospitallevel variability in multivessel disease management noted in our analysis, it appears that local practice patterns may be an important driver of the decisions surrounding staging of procedures as well.…”
Section: Staged Revascularizationmentioning
confidence: 83%
“…Similarly, we did not observe any aortic or mitral valve dysfunction or left ventricular injury, which confirms the safety profile of the Impella 2.5 device with respect to ventricular and valve function and integrity, consistent with previous reports. 7,12,17,18 Analysis of the Kaplan-Meier event curves suggests that the use of a 30-day end point is not sufficient in this population. Other investigations of PCI in severely compromised patients such as the Should We Emergently Revascularize Occluded Coronaries for Cardiogenic Shock (SHOCK) trial 19 and the BCIS-1 study 16 found that event curves continue to diverge over time.…”
Section: Discussionmentioning
confidence: 98%
“…Short-term circulatory support with the device has been demonstrated to be safe and feasible in high-risk percutaneous coronary intervention (PCI) as well as in the setting of hemodynamically stable large anterior ST-elevation myocardial infarction. [14][15][16][17] In patients with CS, a small randomized clinical trial of Impella-2.5 versus IABP demonstrated an improvement in cardiac index in Impella-treated patients. 18 The purpose of the multicenter Impella-EUROSHOCK-registry was to assess procedural safety and outcome of Impella-2.5-support in a large cohort of patients with acute CS.…”
mentioning
confidence: 99%